Opportunities and Risks of Vaccination Progress - Veronika Grimm; Franziska K. Lembcke; Milena Schwarz (Wirtschaftsdienst)
Abstract The success of the vaccination campaign in Germany depends decisively on the availability of vaccines, vaccination capacities and the willingness to vaccinate. On the basis of model calculations, this article presents the possible scenarios of the vaccination progress and discusses requirements for the organisation of the vaccination campaign. It also addresses the long-term perspectives and challenges, e. g. with regard to the vaccination of children and adolescents or the global vaccination progress.